EuReCa_Srbija 2014-2023 - Analysis of data on non-initiation of CPR in relation to the etiology of cardiac arrest - Ristic , Jovana; Medic , Sara; Susković Bosancic, Rajka; Bandulaja , Marina; Vasilic, Milica (Journal Resuscitatio Balcanica, 2024)
Introduction: Cardiac arrest is one of the five leading causes of death in Europe. Timely recognition and application of cardiopulmonary resuscitation (CPR) significantly increase the chances of survival. It is necessary to better understand the reasons for not starting CPR, with the aim that their identification leads to the improvement of guidelines and an increase in survival rates. The Aim: The aim of this study is to analyze the data on the non-initiation of CPR in the context of the etiology of cardiac arrest. Material and Methods: The study included epidemiologic data on out-of-hospital cardiac arrest (OHCA) collected through questionnaires from the EuReCa, European Resuscitation Council (ERC) studies. The criterion for inclusion in the research was a OHCA treated by the emergency medical service (EMS). Pediatric patients were also included in the analysis. The created database consisted of information defined by the unique protocol of the EuReCa ONE study, for the period of October 1, 2014 to December 31, 2023. Results: We found a statistically significant correlation between Utstein and EuReCa etiology of cardiac arrest and the proportion of non-initiation of CPR in recorded cases (p<0.001). The highest percentage of non-initiation of CPR was observed in patients after drowning, where out of 40 recorded cases of submersion, the application of CPR measures was not initiated in any of them, while the lowest percentage of non-initiation of CPR was recorded in electrocution, where out of a total of 15 recorded cases, CPR was not initiated in 5/ 15 (33.33%) cases. The ratio of starting and not starting CPR in the group of patients with cardiogenic cardiac arrest was almost identical, that is, CPR was not started in 3293/6708 (49.1%) cases. Binary logistic regression analysis indicated the female gender as a significant predictor of non-initiation of CPR (p<0.001, OR 2.037, 95% CI 1.880-2.208). Conclusion: This study provides significant data that can contribute to the improvement of strategies for recognition and intervention in out-of-hospital cardiac arrest in Serbia. Additional research and continuous monitoring are needed to determine the influence of etiology, but also of other factors, on the decision not to start CPR.